Galvanic vestibular stimulator for fMRI studies - Della-Justina,Hellen Mathei (2014)
INTRODUCTION: Areas of the brain that are associated with the vestibular system can be activated using galvanic vestibular stimulation. These areas can be studied through a combination of galvanic vestibular stimulation with functional magnetic resonance imaging (fMRI). In order to provide an appropriate sequence of galvanic stimulation synchronous with the MRI pulse sequence, a specific electronic device that was built and assessed is presented. METHODS: The electronic project of the GVS is divided in analog and digital circuits. The analog circuits are mounted in an aluminum case, supplied by sealed batteries, and goes inside the MRI room near to the feet of the subject. The digital circuits are placed in the MRI control room. Those circuits communicate through each other by an optical fiber. Tests to verify the GVS-MRI compatibility were conducted. Silicone (in-house) and Ag/AgCl (commercial) electrodes were evaluated for maximum balance and minimal pain sensations. fMRI experiments were conducted in eight human volunteers. RESULTS: GVS-MRI compatibility experiments demonstrate that the GVS did not interfere with the MRI scanner functionality and vice versa. The circular silicone electrode was considered the most suitable to apply the galvanic vestibular stimulation. The 1 Hz stimulation sinusoid frequency produced the biggest balance and the less pain sensations when compared to 2 Hz. The GVS was capable of eliciting activation in the precentral and postcentral gyri, in the central sulcus, in the supplementary motor area, in the middle and inferior frontal gyri, in the inferior parietal lobule, in the insula, in the superior temporal gyrus, in the middle cingulate cortex, and in the cerebellum. CONCLUSION: This study shows the development and description of a neurovestibular stimulator that can be safely used inside the MRI scanner room without interfering on its operation and vice versa. The developed GVS could successfully activate the major areas involved with multimodal functions of the vestibular system, demonstrating its validity as a stimulator for neurovestibular research. To the best of our knowledge, this is the first work that shows the development and the construction of a galvanic vestibular stimulator that could be safely used inside the MRI room.